WRITING IN TIMES OF DISPLACEMENT the existential and other discourses. - Mbuh, Mbuh Tennu; Chakravorty, Meera; Clammer, J. R. ([S.l.] : ROUTLEDGE, 2022)
This book presents diverse, composite, non-exclusive and non-hierarchical perspectives on displacement of people as represented in literature. It examines the experiences of migration as a result of wars, natural disasters, religious strife, loss of livelihoods and shifts in local and global economies and the vulnerabilities they expose. Bringing together scholarly insights into literature about displacement and migration from Africa, Europe, Asia, and the Middle East, the book interrogates the development frames of Western modernity and situates displacement within the discourse of disenfranchisement of citizens by nation-states. It explores the experiences, memories and expressions of displacement in literature and how literary works critique ethical and moral responsibilities of states and communities that often do not account for the loss which displacement causes to the health, education, career, or relationships of displaced people. The volume will be of great interest to scholars and researchers of literature, philosophy, migration and diaspora studies, development studies, African studies and Asian studies.
Keywords: Refugees in literature; Emigration and immigration in literature; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Emigration & Immigration